Genetic testing for lymphedema-distichiasis syndrome - Rakhmanov Yeltay; Maltese Paolo Enrico; Paolacci Stefano; Marinelli Carla; Bertelli Matteo (The EuroBiotech Journal, 2018)
We studied the scientific literature and disease guidelines to summarize the clinical utility of genetic testing for lymphedema distichiasis (LD) syndrome. LD is inherited in an autosomal dominant manner, and has unknown prevalence. It is caused by variations in the FOXC2 gene. Clinical diagnosis involves clinical examination, targeted at identifying primary lymphedema (chronic swelling of the extremities) and distichiasis (double row of eyelashes). The genetic test is useful for confirming diagnosis, as well as for differential diagnosis, couple risk assessment and access to clinical trials.